1982
DOI: 10.1007/bf01064817
|View full text |Cite
|
Sign up to set email alerts
|

A psychophysiological study of Post Traumatic Stress Disorder in Vietnam veterans

Abstract: Comparisons were made between a group of male Vietnam veterans suffering from Post-Traumatic Stress Disorder (PTSD) (n = 11) and an age and sex matched group of non-veteran controls (n = 11) on their psychophysiological responding (heart rate (HR), blood pressure (BP), forehead EMG, skin resistance level, and peripheral temperature) to mental arithmetic and an audiotape of combat sounds played at gradually increasing volume levels. The two groups responded differently to the combat sounds in terms of HR, systo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
94
2
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 274 publications
(102 citation statements)
references
References 4 publications
5
94
2
1
Order By: Relevance
“…PTSD patients were more distressed than both control groups, by both combat sounds and white noise, supporting the notion of hyper-responsivity to meaningful and ambiguous cues. In agreement with earlier studies (Blanchard et al 1991a;Pitman and Orr 1993), skin conduction and heart rate responses to combat sounds were significantly larger in PTSD, supporting the notion of autonomic hyper-reactivity to trauma-related stimuli and demonstrating that excessive SC and HR responses can be elicited by a "generic" auditory activation paradigm as well as by individualized imagery scripts. SC was a more sensitive index of arousal, responding to both traumatic and nonspecific auditory stimulation; whereas, HR was more specifically responsive to combat sounds.…”
Section: Responsivitysupporting
confidence: 90%
See 2 more Smart Citations
“…PTSD patients were more distressed than both control groups, by both combat sounds and white noise, supporting the notion of hyper-responsivity to meaningful and ambiguous cues. In agreement with earlier studies (Blanchard et al 1991a;Pitman and Orr 1993), skin conduction and heart rate responses to combat sounds were significantly larger in PTSD, supporting the notion of autonomic hyper-reactivity to trauma-related stimuli and demonstrating that excessive SC and HR responses can be elicited by a "generic" auditory activation paradigm as well as by individualized imagery scripts. SC was a more sensitive index of arousal, responding to both traumatic and nonspecific auditory stimulation; whereas, HR was more specifically responsive to combat sounds.…”
Section: Responsivitysupporting
confidence: 90%
“…Among psychophysiological measures, enhanced heart rate (HR) responses have been found consistently reported (Blanchard et al 1982;McFall et al 1990;Pallmeyer et al 1986;); whereas, enhanced skin conductance (SC) and electromyogram (EMG) responses have been mainly reported during internally generated mental imagery Pitman et al 1987). This response heterogeneity is not surprising, because the SC response reflects primarily sympathetic tone, the HR response is governed by both sympathetic and parasympathetic activity, and facial EMG response reflects primarily stimulus appraisal, or valence, but not arousal (Bradley et al 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies (Pitman et al, 1987(Pitman et al, , 1990Blanchard et al, 1982;McFall et al, 1990;Orr et al, 1993;Shin et al, 1999) have investigated psychophysiological reactivity to trauma-related scripts in patients with PTSD. In contrast to the present study, most former studies found more pronounced heart rate responses in PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…We were not able to replicate the findings of larger heart rate responses to traumatic reminders in patients with PTSD. Heart rate differences in response to trauma-related imagery were found in combat-related PTSD in male veterans (Pitman et al, 1987(Pitman et al, , 1990Blanchard et al, 1982;McFall et al, 1990;Orr et al, 1993) and abuse-related PTSD in female patients (Shin et al, 1999;Carson et al, 2000;Orr et al, 1998).…”
Section: Discussionmentioning
confidence: 99%